Inhibition of carbohydrate digestive enzymes by a complementary essential oil blend: in silico and mixture design approaches - Loukili, El Hassania; Fadil, Mouhcine; Elrherabi, Amal; Er-rajy, Mohammed; Taibi, Mohamed; Azzaoui, Khalil; Salghi, Rachid; Sabbahi, Rachid; Alanazi, Mohammed M.; Rhazi, Larbi; Széchenyi, Aleksandar; Siaj, Mohamed; et al. (Frontiers in Pharmacology, 2025)
BackgroundThe increasing demand for natural alternatives in diabetes treatment has driven research into plant-derived metabolites, particularly essential oils (EOs) with bioactive properties. This study aims to optimize an EO mixture for inhibiting two key enzymes involved in glucose digestion: pancreatic α-amylase and intestinal α-glucosidase.MethodsEssential oils were extracted from three Moroccan medicinal plants: false yellowhead (Inula viscosa L.), rose geranium (Pelargonium graveolens L'Hér.), and lemongrass (Cymbopogon citratus (DC.) Stapf.). Gas chromatography-mass spectrometry (GC-MS) analysis identified key metabolites in each EO. A statistical mixture design was employed to evaluate different EO ratios for their inhibitory effects on α-amylase and α-glucosidase. Additionally, density functional theory (DFT) calculations and molecular docking simulations were conducted to assess the key metabolites' electronic properties and interaction potential with target enzymes.ResultsGC-MS analysis identified 32 metabolites in P. graveolens, with citronellol (18.67%), eucalyptol (13.30%), and 2-octen-1-ol (8.12%) as major components. I. viscosa contained 18 metabolites, dominated by 2-camphanol acetate (51.12%) and camphol (19.32%), while C. citratus had 23 metabolites, with α-citral (24.70%) and 2-isopropenyl-5-methylhex-4-enal (29.25%) as key constituents. The optimal formulation for α-glucosidase inhibition was a binary mixture of 73% C. citratus and 27% P. graveolens. In contrast, the best blend for α-amylase inhibition consisted of 56% P. graveolens and 44% I. viscosa. DFT calculations confirmed the electrophilic nature of key metabolites, supporting their potential for enzyme interaction. Molecular docking simulations suggested that these phytochemicals could exhibit stronger inhibitory effects than acarbose, a widely used antidiabetic drug.ConclusionThese findings highlight the potential of optimized EO formulations as natural alternatives for managing hyperglycemia and developing novel diabetes therapies.